Replication Protein A (RPA) Phosphorylation Prevents RPA Association with Replication Centers - Vassin, Vitaly M. (American Society for Microbiology, 2004)
Mammalian replication protein A (RPA) undergoes DNA damage-dependent phosphorylation at numerous sites on the N terminus of the RPA2 subunit. To understand the functional significance of RPA phosphorylation, we expressed RPA2 variants in which the phosphorylation sites were converted to aspartate (RPA2(D)) or alanine (RPA2(A)). Although RPA2(D) was incorporated into RPA heterotrimers and supported simian virus 40 DNA replication in vitro, the RPA2(D) mutant was selectively unable to associate with replication centers in vivo. In cells containing greatly reduced levels of endogenous RPA2, RPA2(D) again did not localize to replication sites, indicating that the defect in supporting chromosomal DNA replication is not due to competition with the wild-type protein. Use of phosphospecific antibodies demonstrated that endogenous hyperphosphorylated RPA behaves similarly to RPA2(D). In contrast, under DNA damage or replication stress conditions, RPA2(D), like RPA2(A) and wild-type RPA2, was competent to associate with DNA damage foci as determined by colocalization with γ-H2AX. We conclude that RPA2 phosphorylation prevents RPA association with replication centers in vivo and potentially serves as a marker for sites of DNA damage.